2023
DOI: 10.1097/hep.0000000000000569
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Wnt signaling promotes HSC glycolysis and liver fibrosis through an LDH-A/HIF-1α transcriptional complex

Feixia Wang,
Li Chen,
Desong Kong
et al.

Abstract: Background and Aims: Aerobic glycolysis reprogramming occurs during HSC activation, but how it is initiated and sustained remains unknown. We investigated the mechanisms by which canonical Wnt signaling regulated HSC glycolysis and the therapeutic implication for liver fibrosis. Approach and Results: Glycolysis was examined in HSC-LX2 cells upon manipulation of Wnt/β-catenin signaling. Nuclear translocation of lactate dehydrogenase A (LDH-A) and its int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
(77 reference statements)
0
0
0
Order By: Relevance
“…The Wnt/β-catenin signaling pathway enhances LDHA stability, promoting glycolysis and liver fibrosis. In mice, the specific deletion of LDHA in HSCs alleviates liver fibrosis ( 146 ). Therefore, the inhibition of LDHA may be an effective treatment for liver fibrosis.…”
Section: Lactate and Lactate Metabolism In The Treatment Of Liver Dis...mentioning
confidence: 99%
“…The Wnt/β-catenin signaling pathway enhances LDHA stability, promoting glycolysis and liver fibrosis. In mice, the specific deletion of LDHA in HSCs alleviates liver fibrosis ( 146 ). Therefore, the inhibition of LDHA may be an effective treatment for liver fibrosis.…”
Section: Lactate and Lactate Metabolism In The Treatment Of Liver Dis...mentioning
confidence: 99%
“…In recent years, studies have shown that the Wnt signaling pathway plays an integral role in the fibrosis in multiple organs(Seo et al 2019 ; Yiu et al 2021 ; Wang et al 2024 ). Glycogen synthase kinase-3β (GSK3β) is a key regulatory factor in the Wnt/β-catenin signaling pathway that maintains the balance between cytoplasmic degradation and nuclear translocation of β-catenin (Guo et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence suggests that metabolic reprogramming is a critical pathological event driving the progression of various disorders, including liver fibrosis, a common consequence of chronic hepatic disorders(Gilgenkrantz et al 2021 ; Trivedi et al 2021 ). Enhanced glycolysis has been regarded as a typical feature of liver fibrosis(Wang et al 2024 ), while inhibition of glycolysis results in beneficial outcomes in experimental animals with liver fibrosis(Xiang et al 2023 ; Li et al 2023 ). However, the molecular mechanisms underlying the detrimental significance of glycolysis in fibrogenesis have not been fully understood.…”
Section: Introductionmentioning
confidence: 99%